1986
DOI: 10.1002/hlca.19860690712
|View full text |Cite
|
Sign up to set email alerts
|

Synthese von Betenamin und von Betalain‐Modellsubstanzen

Abstract: 1. Einleitung. ~ Im Zusammenhang mit unserer Synthese von 17-Decarboxybetanidin (A) durch Pyridin-Ringoffnung [ 11 haben wir auf lhnliche Weise auch einige Modellsubstanzen mit dem charakteristischen Chromophor der Betalaine (der roten und gelben Farbstoffe gewisser Centrospermen Pflanzen [2]) hergestellt. Unter den Produkten ist das Betenamin (B), das Ring-Geriist des roten Riibenfarbstoffs (Randenfarbstoffs) Betanin (C), und einige offenkettige gelbe und rote 1,7-Diazaheptamethinium-Systeme'), speziell auch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…1 H NMR indicates pure product was present. 1 H coupling constant data match those of the previously published compound . Additional material could be isolated with some impurities by stirring the filtrate residue in THF (2 mL, 0.0075 g, 0.017 mmol, 15% without adjustment for impurity).…”
Section: Methodssupporting
confidence: 77%
See 1 more Smart Citation
“…1 H NMR indicates pure product was present. 1 H coupling constant data match those of the previously published compound . Additional material could be isolated with some impurities by stirring the filtrate residue in THF (2 mL, 0.0075 g, 0.017 mmol, 15% without adjustment for impurity).…”
Section: Methodssupporting
confidence: 77%
“…A series of control experiments determined that light and water were requirements for satisfactory formation of 11 but that oxygen was detrimental to its preparation in the presence of light. Proton NMR, HRMS, and UV−vis data (λ max = 525 nm) confirmed that 11 was the indoline cyanine shown below, previously synthesized from 1-(2,4-dinitrophenyl)pyridinium chloride . Repeating the photolysis in the presence of an excess of free indoline increased the NMR yield of 11 to 80% (eq ). …”
Section: Resultsmentioning
confidence: 99%
“…The chemical versatility of betanin has led to its application as a redox mediator in dye-sensitized solar cells [17] and hydrogen production systems [18,19], for the synthesis of metal nanoparticles [20], as an anti-inflammatory agent [21], and as an antioxidant [22]. The antioxidant capacity of betanin is comparable to that of ECG due to the presence of a 5- O -glucosyl catechol moiety and a 1,7-diazaheptamethinium [23] system [24,25,26]. We have found that N -(3-hydroxylphenyl)betalain ( m -OH-pBeet) is an adequate model to study the mechanism of antioxidant action of betanin because they share the same radical scavenging capacity [27].…”
Section: Introductionmentioning
confidence: 99%